2016
DOI: 10.1016/j.joad.2016.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Clinical epidemiology and treatment findings of acute tuberculosis patients in Babol City (2009–2013)

Abstract: A B S T R A C TObjective: To examine the clinical epidemiology and treatment findings of tuberculosis in Babol, Northern Iran. Methods: This cross-sectional study was carried out on medical records of tuberculosis registry pertaining to health center of Babol City, Mazandaran, Iran. The investigated variables included demographic characteristics and some clinical patterns of patients. To present the findings, the descriptive statistics such as mean (and SD) and frequency (%) was used. Analytical statistics was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…the ratio of urban and rural patients was almost identical, however, men suffered from tuberculosis 1.5 times more than women. In this study, only three patients had HIV [20]. In another study in Tehran, while the ratio of men and women was similar, in this study, the proportion of urban patients was four times more than rural patients [21].…”
Section: Discussionsupporting
confidence: 52%
“…the ratio of urban and rural patients was almost identical, however, men suffered from tuberculosis 1.5 times more than women. In this study, only three patients had HIV [20]. In another study in Tehran, while the ratio of men and women was similar, in this study, the proportion of urban patients was four times more than rural patients [21].…”
Section: Discussionsupporting
confidence: 52%
“…'s () and Nikbakht et al. 's () studies averaged in age between 31.7–47.5 years. Overall, the results indicated that gender, age, education, income and employment are correlated with TB, despite differences in geographic location or culture.…”
Section: Discussionmentioning
confidence: 96%
“…Tuberculosis is a chronic infectious disease, caused by the bacterium Mycobacterium tuberculosis. With regular medication, 90%-95% of patients can be fully cured in 6-9 months (Nikbakht et al, 2016;Wu, Lu, Chen, Pan, & Feng, 2011). TB incidence in the USA remained at approximately 3.0 cases per 100,000 persons during -2015(Salinas et al, 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Noeske et al also reported that most of the TB patients belonged to the age group of 25-34 years in Cameroon (5). In a study in Hamedan province, Khazaei et al (6) reported that the largest TB cases occur in the age group over 60 years old, which is more consistent with the TB pattern of the whole country (7). It seems that the high number of affected people in the age group of 20-39 years old is due to the high population of this age group and the high prevalence of addiction among them.…”
Section: Resultsmentioning
confidence: 76%